Addressing the Needs of Victims: The Standpoint of Crime Victims Within the Obuasi Municipality - Ofori-Dua, Kwadwo; Azumah, Francess Dufie; Nachinaab, John Onzaberigu; Mohammed, Muazu (Journal of victimology and victim justice (Print), 2022)
The criminal justice system lacks the protection for most victims and does not provide adequate compensation and rewards for an injury that individuals incurred during a crime experience to meet crime victims’ needs. After victims report a crime, they expect the judicial system to deliver justice to meet their needs in addressing their concerns. However, this is lacking in the criminal justice system. The focus of the study was to identify measures put in place to identify and address victims’ needs. Purposive and snowballing sampling techniques were used. Data were collected from 35 respondents; mainly crime victims and officials of the criminal justice system in the Obuasi Metropolis. A qualitative approach was adopted. The study found that the first step the victims felt their needs could be identified and addressed was, their point of reporting of crime incidence to the police but that was never the case. Hence, most crime victims want payback (replacement of lost properties), compensation and rewards from the offenders. According to most victims, imprisoning perpetrators alone does not meet victims’ needs. As crime had already been committed and nothing could be done to turn back the clock. This calls for more pragmatic approaches in addressing crime victims’ needs within the criminal justice system.